News televisions' impact on political discourse in the Indian election 2014. (1st June 2016) - Ranganathan, Maya
The Indian national election of 2014 has been studied intensely mainly because of the scale of the Bharatiya Janata Party (BJP) victory and the ingenious ways new technologies were employed for political communication. The role of news television in democratic politics has been questioned in the context of Indian media's unbridled efforts towards profit-maximization since private television began in the 1990s, and the impact of these efforts on media credibility. This article asserts that television still shapes and directs political discourse, even in the age of new technologies, but that the role of news television in political communication needs to be rethought. It argues that the evaluation of news television's agenda setting functions must be placed not only within the context of the dramatic changes that have swept the Indian media landscape but within broader changes in the political and social environments. A critical discourse analysis of Frankly Speaking, the popular weekly political interviews shown on the English news channel Times Now, reveals the subtle ways by which television transfers salience from the media's agenda to the public agenda.